SOURCE STUDIES OF THE CONSTRUCTION OF THE MIRZO ULUGBEK HIGHER MADRASAH IN SAMARKAND - Imamov Ulug’bek Ismailovich (Journals Park Publishing, 2023)
In the history of the culture of Central Asia, the reign period of Timur and the Timurids, from the second half of the XIV century to the beginning of the XVI century, is an extremely bright, rich, productive period that had a great impact on the recent general historical development. During this period, the Uzbek language as a literary language, direct Turkic written culture was fully formed and determined the latest development of Central Asia in this field. The last Timurids - the son, grandson and descendants of Amir Temur tried to continue the direction of social and cultural life started by Timur, to preserve the traditions of the Timurid family. The flourishing of the culture of Central Asian urban planning, beautification, and creative works continued during the Timurid period. This is especially evident during the reign of Amir Temur's grandson Ulugbek. This article contains valuable information about the history of the construction of the Mirzo Ulugbek’s Higher Madrasah.
Keywords: Madrasah, kufi and rayhani manuscripts, turkish written culture, architecture, geography, karya (village), general composition, city structure, khagani said, mudarris, mausoleum, respected religious figure, nobility and clergy, source studies.